List of IMF Member Countries with Delays in Completion of Article IV Consultations or Mandatory Financial Stability Assessments over 18 Months. (Policy Papers; Policy Paper ;, 2019)
In line with the framework for addressing excessive delays in the completion of Article IV consultations, the following table lists the IMF members for whom the Article IV consultation has been delayed by more than 18 months as of December 15, 2018.